2016
DOI: 10.3389/fpsyg.2016.01639
|View full text |Cite
|
Sign up to set email alerts
|

How to Make Nothing Out of Something: Analyses of the Impact of Study Sampling and Statistical Interpretation in Misleading Meta-Analytic Conclusions

Abstract: The limited resource model states that self-control is governed by a relatively finite set of inner resources on which people draw when exerting willpower. Once self-control resources have been used up or depleted, they are less available for other self-control tasks, leading to a decrement in subsequent self-control success. The depletion effect has been studied for over 20 years, tested or extended in more than 600 studies, and supported in an independent meta-analysis (Hagger et al., 2010). Meta-analyses ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 42 publications
1
77
0
Order By: Relevance
“…It is also likely that publication bias has obscured an understanding of the nature and parameters of a depletion effect, although there has been significant disagreement regarding criteria for inclusion and exclusion in depletion meta‐analyses (e.g., Carter & McCullough, ; Cunningham & Baumeister, ). Recent proposals that researchers preregister their intended experimental protocols (e.g., Hagger et al ., ) would be of significant benefit in addressing this problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also likely that publication bias has obscured an understanding of the nature and parameters of a depletion effect, although there has been significant disagreement regarding criteria for inclusion and exclusion in depletion meta‐analyses (e.g., Carter & McCullough, ; Cunningham & Baumeister, ). Recent proposals that researchers preregister their intended experimental protocols (e.g., Hagger et al ., ) would be of significant benefit in addressing this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Although they observed a statistically significant depletion effect under some analytic conditions, they concluded that the overall pattern of results suggested that the depletion effect was not robust and was not significantly different from zero (Carter et al, 2015). However, this meta-analysis was itself criticized on methodological grounds by Cunningham and Baumeister (2016), who observed that replication failures may be attributable in part to methodologically weak studies conducted by inexperienced researchers, as evidenced by a high proportion of graduate student authorship among the unpublished depletion studies included in the Carter et al (2015) meta-analysis. In addition, the authors criticized a failure to address research quality, and failure to assess whether tasks were adequately operationalized.…”
mentioning
confidence: 97%
“…Not only researchers disagree about whether willpower relies on a limited resource or is nonlimited (Cunningham & Baumeister, ; Hagger et al, ; Inzlicht, Schmeichel, & Macrae, )—lay people, too, have their own varying beliefs about how willpower works, regardless of whether or not they have consciously thought about the topic. Some people believe that willpower is limited and that mental exertion results in fatigue, while others believe that willpower is nonlimited and that mental exertion can even be energizing.…”
Section: Introductionmentioning
confidence: 99%
“…We used the same tasks in Study 1 that were used in the multi-lab replication project of ego depletion (Hagger et al, 2016), which uses a computerized version of the letter-e task. This computerized task has been criticized because it may not be depleting enough to yield an ego-depletion effect (Baumeister & Vohs, 2016): instead of establishing a habit first by letting the participants cross out each instance of the letter 'e', both the replication project and the original study (Sripada et al, 2014) skip this habit-forming step; as a result, there is no habit that needs to be overridden effortfully. However, research shows that the computerized letter-e task is as effective in invoking performance decrements as the pen-and-paper version (Arber et al, 2017).…”
Section: Limitationsmentioning
confidence: 99%